Characterization antagonism of Nigrospora spp. against Fusarium solani causing Fusarium wilt in Capsicum frutescens L. plants - Supiana Dian Nurtjahyani; M. Rafi Dhiaulhaq; Moh. Ilham Yusuf; Ali Mustofa (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2026)
Fusarium wilt is a major disease affecting horticultural crops in Indonesia, including chili, where it causes root rot, disrupts nutrient uptake, and reduces plant growth. This study aimed to evaluate the antagonistic activity of five Nigrospora spp. isolates against Fusarium solani, the causal agent of Fusarium wilt in chili plants (Capsicum frutescens L.). The tested isolates included Nigrospora gorlenkoana, N. guilinensis, N. musae, N. oryzae, and N. rubii. Antagonistic activity was assessed using the dual culture method on potato dextrose agar (PDA) at 25 ºC for 72 hours. The results showed that all isolates inhibited the growth of F. solani, with N. rubii exhibiting the highest inhibition (56.2%), followed by N. oryzae (50.0%), N. gorlenkoana (30.4%), and N. musae (28.2%), while N. guilinensis showed the lowest inhibition (9.3%). The antagonistic mechanisms involved competition for nutrients and space, as well as mycoparasitism. These findings indicate that N. rubii and N. oryzae are promising candidates for biological control of Fusarium wilt in chili, offering environmentally friendly alternatives to chemical fungicides. This study provides comparative evidence of species-specific antagonistic activity and highlights the potential of Nigrospora spp. for sustainable disease management.